A compreensão de pais acerca da importância da participação familiar no cuidado de crianças com transtorno fonológico - Fernandes, Delta Regina (Universidade Federal de São Carlos, 2018)
The speech sound disorder (SSD) has a high prevalence among children and it is characterized by mistakes in the production, perception and mental organizations of the sound of speech. Early recognition and appropriate speech intervention reduce the risks of harm, such as difficulties in reading and writing acquisition and development, as well as the emotional, social and cognitive shortfalls in children. Considering that active family involvement is indispensable to therapeutic efficiency, this research aim is to understand parents' and caregivers’ perceptions of children in speech treatment regarding the importance of family involvement in the process of care. Through a clinical qualitative study, thirteen parents and caregivers were interviewed, and their speech was subjected to the analysis of its thematic content. The findings were interpreted regarding the Humanization in Health Care, Patient-centered Care and Family-centered Care. It was found that the subjects had SSD awareness and waited for the phonological reorganization of the language and its secondary gains. Family participation in the caring process was recorded through its attendance during the clinical sessions and the achievement of procedures assigned by the speech and language therapists to be done at home. Some of the families regarded their involvement as important and participated actively. Others, nonetheless, reinforced that contextual and personal problems made their involvement in the therapeutic project outside of the ambulatory scenario difficult. There were also, families who did not understand the need for their involvement and focused their critics on the assistance. Therefore, it is important that the practitioner regards the singularity of the SSD, with its meanings and repercussions for children, their caregivers, and family in the therapeutic project, to go beyond the reorganization of the phonological aspects of the language. Speech and language therapists need to understand the sufferings the SSD cause both children and their caregivers as well as the possibility of the increase of these sufferings due to expectations not yet fulfilled during treatment.
Parents' understanding of the importance of family involvement regarding care of speech sound disorder children
Keywords: Cuidadores; Assistência centrada no paciente; Transtorno fonológico; Pesquisa qualitativa; Caregivers; Patient-centered care; Speech sound disorder; Qualitative research; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA